La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Centre de recherche interuniversitaire sur la littérature et la culture au Québec [CRILCQ], 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Vivier reenacted: Singing beyond masculine - Novak, Jelena (New Sound: International Magazine for Music, 2015)
Vivier: A Night Report is a kind of poetical archive of musical details, protocols, experiences, concepts, memories, fears, desires and sorrows connected to Canadian composer Claude Vivier's (1948-1983) unusual destiny. All characters from Marko Nikodijević's opera originate from Vivier's life and works but they are re-indexed, or reenacted differently. The countertenor voice of Vivier is what primarily makes him different from all the rest of the characters. Even it could be claimed that the rest of the voices are dominated by Vivier's vocal presence on stage. Vivier stands as symbol for minority, queer, vulnerable. During his short life he was trying to get his own voice, voice as the personification of freedom and possibility to be heard. Finally he gets vivid, imaginative opera in which both his physical and personified voices are shining by creativity that his art emanate. He gets his singing voice, and he finally gets heard.